Scientific American. – 1869. – Vol. 20, № 13 - б/а (New York. Munn & Company, 1869)
A weekly journal of practical information, art, science, mechanics, chemistry and manufactures.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; Research Subject Categories::NATURAL SCIENCES; Research Subject Categories::TECHNOLOGY; March 27, 1869